2017
DOI: 10.1680/jgeot.15.p.099
|View full text |Cite
|
Sign up to set email alerts
|

A centrifuge study of the seismic response of pile–raft systems embedded in soft clay

Abstract: A series of centrifuge tests were performed on a 4 × 3 pile–raft system embedded in soft kaolin clay to investigate the pile bending moment and raft acceleration response under seismic excitation. Two types of far-field ground motions were employed, these being representative of the short- and long-duration ground motions arising from the Great Sumatran Fault and the Sunda Subduction Trench, respectively. The influences of the peak base acceleration, pile type and raft mass on raft acceleration and pile bendin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…However, a very limited amount of experimental data is available on the dynamic behaviour of pile foundations in soft clay. The few centrifuge experimental studies on clays with pile foundations (Rashidi 1994;Wilson 1998;Banerjee 2009;Zhang et al 2017) are all for end-bearing pile foundations, in which most of them observed amplification in pile foundations and clay response for the different intensities of shaking. In contrast, Idriss (1990) predicts significant amplification in soft clays for low to medium bedrock accelerations up to 0.3 g and attenuation for stronger bedrock accelerations, based on equivalent linear analyses.…”
Section: Problem Definition and Backgroundmentioning
confidence: 99%
“…However, a very limited amount of experimental data is available on the dynamic behaviour of pile foundations in soft clay. The few centrifuge experimental studies on clays with pile foundations (Rashidi 1994;Wilson 1998;Banerjee 2009;Zhang et al 2017) are all for end-bearing pile foundations, in which most of them observed amplification in pile foundations and clay response for the different intensities of shaking. In contrast, Idriss (1990) predicts significant amplification in soft clays for low to medium bedrock accelerations up to 0.3 g and attenuation for stronger bedrock accelerations, based on equivalent linear analyses.…”
Section: Problem Definition and Backgroundmentioning
confidence: 99%
“…The base motion with a peak acceleration of 0.06g shown in Fig 1(a) represents a type of far-field shaking event that may be felt in Singapore. It is a synthesized signal with reference to the past seismic-induced motions measured in Singapore, which was also used by Zhang [ 45 ] and Zhang et al [ 46 ] for both the centrifuge tests and FE analyses. In addition, the ground motions shown in Fig 1(b) and 1(c) were compiled based on two horizontal earthquake records (east-west direction) measured at Stations El Monte-Fairview Av and TTN005 during the 1992 Landers and 1999 Chi-Chi earthquakes, respectively.…”
Section: Input Far-field Ground Motionsmentioning
confidence: 99%
“…For tangential behaviour, the friction coefficient was set equal to 0.4663, which was obtained by assuming a frictional angle the same as that of clay. The effect of friction coefficient is not included in this study, while preliminary separate numerical analyses suggest that the effect of friction coefficient is minimal for input base motions with peak base accelerations (PBA) less than or equal to 0.12 g and considerable for PBA = 0.24 g. Following the in-flight T-bar test results during centrifuge tests on normally consolidated clays reported by Zhang [ 45 ] and Zhang et al [ 46 ], the shear stress limit was set equal to 0.24 σ’ v in kPa, where σ’ v is the effective overburden pressure of the clay at the depth of interest.…”
Section: Numerical Modelling Proceduresmentioning
confidence: 99%
“…Banerjee et al (2014) carried out centrifuge tests to examine seismic effects on fixed-head, end-bearing piles installed through soft clay. Other previous studies related to the seismic response of pile foundations in soft ground can be found in the literature (Wilson et al 1997;Wilson 1998;Boominathan and Ayothiraman 2006;Zhang et al 2017;Garala and Madabhushi 2019;Yang et al 2019). In addition to these laboratory tests, the measured seismic response data of a real bridge constructed on soft clay ground were used to develop finite element models to assess the soil-foundation-support performance under long-term conditions (Mayoral et al 2009).…”
Section: Introductionmentioning
confidence: 99%